대장샘암종의 눈꺼풀 전이 1예 - 황신영; Shin Young Hwang; 오동은; Dong Eun Oh (Daihan angwa haghoi jabji, 2015)
목적: 좌측 위눈꺼풀에 전이된 대장샘암종 1예를 경험하였기에 보고하고자 한다. 증례요약: 73세 남자 환자가 10일 전 발견한 좌측 위눈꺼풀의 종괴를 주소로 내원하였다. 과거력상 2년 전 직장암 발생 및 간, 폐전이를 확인하였고 대장암 수술 후 항암치료를 받았다. 안와 전산화단층촬영상 좌측 위눈꺼풀에 10.7×14.7×9.0 mm 크기의 종괴가 보였으며 조직검사상 위눈꺼풀에 전이된 대장샘암종으로 확인되었다. 근치적 절제는 불가능하여 용적축소수술을 시행하였으며 보존적 치료를 하면서 경과관찰하였으나 환자는 수술 3주 후 사망하였다. 결론: 눈꺼풀의 전이성 종양은 매우 드물며 특히 전이성 대장샘암종은 아주 드문 질환이다. 악성 종양의 병력이 있는 환자에서 발생한 눈꺼풀 병변은 반드시 조직 검사를 통해 정확한 진단을 하고 이에 맞추어 치료 방향을 결정해야 할 것이다. <대한안과학회지 2015;56(6):950-955> Purpose: To report a metastatic colonic adenocarcinoma in the left upper eyelid. Case summary: A 73-year-old male presented to our clinic with a palpable mass in his left upper eyelid that had appeared 10 days prior. The patient had a history of colon cancer that was diagnosed 2 years previously with liver and lung metastases, and he had underwent colon resection followed by chemotherapy. A 10.7 × 14.7 × 9.0 mm mass was observed on orbital computed tomography and a biopsy confirmed that the mass was a metastatic colonic adenocarcinoma. Because radical resection of the mass could not be performed, a debulking surgery was performed instead. The patient was followed up while receiving conservative treatment, but he died 3 weeks after surgery. Conclusions: Metastatic tumors in the eyelids are very rare and colonic adenocarcinoma metastases in the eyelids are even less common. Thus, a biopsy examination and appropriate treatment should be administered to patients with a history of malignancy who present with an eyelid mass.J Korean Ophthalmol Soc 2015;56(6):950-955